Application of the HEC-HMS hydrological model in the Beht watershed (Morocco) - Daide Fatima (EDP Sciences, 2021)
This work focused on the collection and preparation of the data required for the hydrological modelling of the Beht catchment area, which covers an area of 4560 km2 with a perimeter of 414 km, by combining the various spatial technologies, in particular geographical information systems (GIS), remote sensing, and digital terrain models (DTM), with hydrological models in order to prepare for spatial hydrological modelling used for flood forecasting. The methodology consists, at first, in the automatic extraction of the sub-basins and the drainage network. Then, edit these data using the HEC-GEO-HMS extension, and the preparation of the land use and land cover data for the elaboration of a Curve Number (CN) map of Beht watershed, then the import of the basin model into the Hydrologic Modeling System (HEC-HMS) to simulate the surface runoff using six extreme daily time series events.